ملف الانجاز كأسلوب بديل ومتكامل في التقويم التربوي - عزي, ايمان; اسعادي, فارس (جامعة الوادي - University of Eloued, 2021)
إن النظرة الشمولية لعملية التعليم و التعلم تتطلب نظرة شمولية لعملية التقويم التربوي من أجل تقديم معلومات شاملة عن مستوى تعلم الطلبة و مساعدتهم على تحديد نواحي القوة و الضعف في تعلماتهم, فالنظرة الحقيقية للتعليم و التعلم لم تعد تركز على التحصيل الأكاديمي فقط و إنما أصبحت تدفع التربويين إلى تبني مخرجات تعليمية عالية المستوى و إخراج طلبة متعلمين متطلعين لما يحيط بهم و مفكرين جيدين, معالجين للمعلومات بمهارة, و متعاونين قادرين على التعلم ذاتيا.فمن هذا المنطلق ظهرت الحاجة لتبني طرائق و أساليب تقويمية بديلة عن تلك التقليدية المنحصرة في تطبيق الاختبارات التحصيلية للحكم على مدى تقدم الأفراد في العملية التعليمية فهي أشبه بكاميرا التصوير العادية التي لا تعطينا إلا صورة ثابتة عن الفرد ولا تدل على كل حركاته و أطوار نموه, و لعل أبرز هذه الأساليب التقويمية البديلة هو التقويم من خلال ملفات الانجاز ،فما هي ملفات الانجاز؟ و ما أليات العمل بها في عملية التقويم؟ . Abstract: The holistic view of the education and learning process requires a holistic view of the educational calendar process in order to provide comprehensive information on the level of learning of students and help them determine the strengths and weaknesses of their learning, the real view of education and learning no longer focuses only on academic achievement, but is pushing educators to adopt high-level educational outcomes and to bring out educated students looking forward to what surrounds them and good thinkers From this point of view, there is a need to adopt methods and methods of evaluation alternative to those traditional limited to the application of collective tests to judge the progress of individuals in the educational process, it is like a regular camera that gives us only a fixed image of the individual and does not indicate all his movements and developmental phases, and perhaps the most prominent of these alternative calendar methods is the calendar through achievement files, what are the achievement files? And what are the mechanisms to work on in the calendar process?
Completion file as an alternative and integrated in the educational calendar
مقال
Keywords: التقويم التربوي؛ ممفات االنجاز.; Educational calendar, achievement files.